L’INFLUENCE DES SELS MINERAUX ET L’IMPORTANCE DE SELENIUM SUR LA REPRODUCTION CHEZ LA VACHE - Mezhoud, Abderrazak (My University, 2021)
Reproduction is an essential function in suckling and dairy farms since their profitability depends on it. It is the first function affected in case of dietary error. This is why deficiencies or excesses in trace elements and vitamins are more easily apparent and identifiable. Among the diseases that appear when there are deficiencies in minerals and vitamins are: placental retention, infertility, early embryonic death.
Keywords: reproduction, breeding, trace elements, vitamins, deficiencies